Social Media and Student Entrepreneurial Behaviour in The New Normal Era - Susilowati, Rini; Veranita, Mira; Gunardi, Gunardi (Operations Research: International Conference Series, 2022)
The global Covid-19 pandemic has had an impact on the Indonesian people's health, economic situation, education, and social life. The most visible impact is financial difficulties in the family, as the family economy is deteriorating as a result of different social limitations that disrupt community economic activity. Despite the economic slump, many students appear to be inspired to establish a business and succeed in earning money to help support their families' financial situation. This study uses qualitative approaches to investigate the effect of social media in student entrepreneurial behavior, with 31 students serving as informants who have created and run businesses since the pandemic hit Indonesia. Data collection techniques are through observation, interviews, documentation studies and triangulation, with analytical techniques: Data Reduction, Data Display and Conclusion Drawing. All the results of the research data were processed using the data analysis technique of the Miles and Huberman model. The study's findings suggest that, in this digital age, social media may help students become great businesspeople who never give up, are confident, have mental-emotional resilience, can read possibilities and opportunities, and are always learning and increasing their knowledge. Students who create businesses are mostly motivated by a desire to help their families' financial situation, which is deteriorating. The implications of this research are:, in addition to generating business motivation, social media can assist business students in developing their businesses by promoting products, building relationships with consumers, suppliers, and competitors, as well as receiving direct feedback that can be used to improve product and service quality in a simple and relatively inexpensive manner. Obstacles include a lack of expertise and creative ability to develop fascinating content at the same time, as well as limitations imposed by society's value system, which restricts the amount of space available for commercial operations.